Actividad de colinesterasa plasmática y sintomatología presente en fumigadores del valle de Mala, expuestos a plaguicidas anticolinesterásicos - Huamaní-Pacsi, C. (2005)
As previous studies have reported that long-term exposure tu pesticides anticholinesterases (organophosphates and carbamates) at repeated dose produces neurotoxicity, it has determinated the plasma cholinesterase activity and the symptomatology in 83 pesticides applicators from valley of Mala-Perú with the purpose to knowing the exposure levels and to have an indication oí the health effects in the applieators. The control group consisted of 28 subjects who were matched with the sociodemographics characteristics of the applicators but whose economical activíty was difierent to agriculture. It was found that the studied applicators did not fulfill the protection rules during the manage of pesticides. The mean of plasma cholinesterase activity in 4 from 5 formed groups by the proccedence place of applícators were significatively lower than the mean of the control group. The 5 symptoms more found were headache (62%), blurred vision (52%), dizziness (37%), salivation (32%) y sweating (31%). With the found results in the studied applicators, we conclude that their exposure levels to pesticides anticholinesterases vary widely and their symptoms were re1ated te their occupation.